2012
DOI: 10.5489/cuaj.116
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in practice patterns and associated outcomes for upper tract urothelial carcinoma in Canada

Abstract: Introduction: We delineated Canadian regional differences in practice patterns in the management of upper tract urothelial carcinoma (UTUC) after nephroureterectomy and relate these to patient outcomes. Methods: A database was created with 1029 patients undergoing radical nephroureterectomy for UTUC between 1994 and 2009 at 10 Canadian centres. Demographic, clinical and pathological variables were collected from chart review. Practice pattern variables were defined as: open versus laparoscopic nephroureterecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…While the risks/benefits of lymphadenectomy are still being debated, the actual proportion of patients undergoing simultaneous lymphadenectomy during NU is very limited. In 2012, the Canadian Upper Tract Collaboration (CUTC) summarised different practice patterns zone wise across 10 institutions and included data of 1029 patients of UTUC [19]. Proportions of patients with pNx nodal stage were 69%, 80% and 70% across central, east and western regions of the country, respectively.…”
Section: Trends In Lymphadenectomymentioning
confidence: 99%
“…While the risks/benefits of lymphadenectomy are still being debated, the actual proportion of patients undergoing simultaneous lymphadenectomy during NU is very limited. In 2012, the Canadian Upper Tract Collaboration (CUTC) summarised different practice patterns zone wise across 10 institutions and included data of 1029 patients of UTUC [19]. Proportions of patients with pNx nodal stage were 69%, 80% and 70% across central, east and western regions of the country, respectively.…”
Section: Trends In Lymphadenectomymentioning
confidence: 99%
“…3). Five studies including LNU (n=1126) and ONU (n=1403) (Ariane et al 2012;Fairey et al 2013;Favaretto et al 2010;Metcalfe et al 2012;Terakawa et al 2008) reported the UnRFS. The pooled analysis of the available HRs showed that the different surgical procedures were not significantly correlated with disease recurrence (HR 1.10, 95% CI: 0.93-1.28; P = 0.337, I 2 = 12.0%; Fig.…”
Section: Oncological Recurrencementioning
confidence: 99%
“…Among the four studies that provided the HRs of OS, there were 1442 LNU patients and 3119 ONU patients. (Fairey et al 2013;Kim et al 2015;Metcalfe et al 2012;Rieken et al 2014) There was significant heterogeneity ( P = 0.091, I 2 = 53.7%; Fig. 5), and a random model was applied.…”
Section: Mortalitymentioning
confidence: 99%
“…[1][2][3][4][5] Approximately 20-40% of patients initially present with locally advanced disease and lymph node (LN) metastases at the time of diagnosis. [6][7][8][9] Recently, Margulis et al identified age, high tumour grade, high pathological T stage, LN metastasis, sessile architecture, an infiltrative growth pattern, and lymphovascular invasion (LVI) as independent prognostic indicators of disease recurrence and cancer-specific survival (CSS).…”
Section: Introductionmentioning
confidence: 99%